Christian Humanism and Psychotherapy: A Response to Bergin's Antitheses - Curry, John F. (Zygon, 1987)
Abstract. Secular and religious values of psychotherapists influence the process of psychotherapy. The psychologist Allen Bergin has pointed out several major antitheses between values of secular psychotherapists and their religiously oriented clients. The present essay is a response to Bergin's antitheses, on the one hand, and to humanistic psychology, on the other, from the point of view of a Christian humanism. Karl Rahner's theological anthropology is proposed as one possible foundation for an explicit articulation of the relationship between psychotherapy and religion, and as a means to address apparently divergent values of psychotherapists and religious believers.